Preparation and Characterization of Chitosan/Agar Blended Films: Part 1. Chemical Structure and Morphology - Esam A. El-hefian; Mohamed Mahmoud Nasef; Abdul Hamid Yahaya (E-Journal of Chemistry)
Chitosan/agar (CS/AG) films were prepared by blending different proportions of chitosan and agar (considering chitosan as the main component) in solution forms. The chemical structure and the morphology of the obtained blended films were investigated using Fourier transform infrared (FTIR) and field emission scanning electron microscope (FESEM). It was revealed that chitosan and agar form a highly compatible blend and their films displayed homogenous and smooth surface properties compared to the individual pure components.